2010
DOI: 10.1016/j.ydbio.2010.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Wnt/β-catenin signaling in the dental mesenchyme regulates incisor development by regulating Bmp4

Abstract: Loss- and gain-of function approaches modulating canonical Wnt/β-catenin activity have established a role for the Wnt/β-catenin pathway during tooth development. Here we show that Wnt/β-catenin signaling is required in the dental mesenchyme for normal incisor development, as locally restricted genetic inactivation of β-catenin results in a splitting of the incisor placode, giving rise to two incisors. Molecularly this is first associated with down-regulation of Bmp4 and subsequent splitting of the Shh domain a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
66
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 58 publications
3
66
0
Order By: Relevance
“…The upregulation of Efna2 and Efna4 in the β-catenin mutant cells might not be related to corneal epithelial stratification. Among all of the upregulated cytokines in the β-catenin mutant, only Bmp4 has previously been reported to be a downstream target of Wnt/β-catenin signaling (Baker et al, 1999;Fujimori et al, 2010). Therefore, we addressed the possible involvement of Bmp4 in the observed phenotype and found that Bmp4 indeed plays an important role in corneal epithelium development.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The upregulation of Efna2 and Efna4 in the β-catenin mutant cells might not be related to corneal epithelial stratification. Among all of the upregulated cytokines in the β-catenin mutant, only Bmp4 has previously been reported to be a downstream target of Wnt/β-catenin signaling (Baker et al, 1999;Fujimori et al, 2010). Therefore, we addressed the possible involvement of Bmp4 in the observed phenotype and found that Bmp4 indeed plays an important role in corneal epithelium development.…”
Section: Discussionmentioning
confidence: 94%
“…For example, in Xenopus Wnt/β-catenin signaling contributes to the repression of Bmp4 on the dorsal side of the embryo and sensitizes the ectoderm to respond to neural-inducing signals (Baker et al, 1999). In the mouse dental mesenchyme, Wnt/β-catenin signaling regulates Bmp4 expression during incisor development (Fujimori et al, 2010). However, the possible cross-talk between these two signaling pathways during mouse corneal epithelium stratification has not been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…These epithelially expressed Wnts also act on dental mesenchyme and form a Wnt-BMP feedback circuit with mesenchymally expressed BMP4 to mediate epithelialmesenchymal interactions during early tooth development (O'Connell et al, 2012). The requirement of β-catenin signaling in the dental mesenchyme for early tooth development was manifested by the arrested molar development at the bud stage and the splitting of the incisor placode in mice carrying tissue-specific inactivation of Catnb in the dental mesenchyme Fujimori et al, 2010), although the contribution to the phenotype by impaired cell adhesion in the absence of β-catenin cannot be ruled out. However, whether active β-catenin signaling is operating in the mesenchyme of the early developing tooth remains arguable.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, constitutive activation of β-catenin signaling in oral epithelium induces ectopic tooth formation Liu et al, 2008). Although β-catenin signaling activity is present in the dental mesenchyme of the E12.5 incisor (Fujimori et al, 2010), such activity has never been reported in the incisor mesenchyme beyond E12.5 and was not detected in developing molar mesenchyme using several Wnt/β-catenin signaling reporter mouse lines, including BATGAL, TOPGAL and TCF/Lef-lacZ mice (Liu et al, 2008), suggesting that Wnt/β-catenin activity is maintained at a very low level, if any, in the dental mesenchyme. Elevated Wnt/β-catenin signaling results in the formation of bone-like tissues in the dental pulp Li et al, 2011a).…”
Section: Introductionmentioning
confidence: 99%
“…Epithelial Bmps induce the expression of Bmp4 in the mesenchyme before bud stage correlating with the shift in the odontogenic potential (Vainio et al 1993). Also, Wnt/b-catenin signaling in the incisor mesenchyme stimulates the expression of Bmp4 that in turn regulates Shh in the epithelium (Fujimori et al 2010). Furthermore, Wnt signaling was shown to be required in the molar mesenchyme for the bud to cap stage transition and primary enamel knot formation (Chen et al 2009).…”
Section: Signaling Network Regulating Tooth Developmentmentioning
confidence: 99%